The reality of ISO 22301 business continuity management in the public sector to face crisis: the Kingdom of Saudi Arabia as a model - Alghamdi, Asma Abdulrahman (Journal of Risk and Crisis Management, 2022)
This research seeks to shed light on the reality of business continuity management in the public sector to face crises in the Kingdom of Saudi Arabia. The ISO 22301 standard for business continuity was adopted to measure reality, and the results showed that some public sector organizations adopted a business continuity management system according to the ISO standard. and the current research was presented Many recommendations and proposals that ensure the development of business continuity management in the public sector in the Kingdom of Saudi Arabia in order to preserve the efficiency of public sector performance in the face of crises.